The Contextual Teaching and Learning Using Media for Student Character Formation: Pengajaran dan Pembelajaran Kontekstual Menggunakan Media untuk Pembentukan Karakter Siswa - Fitri Ana, Miko; Syahri , Moh; Tinus , Agus (Academia Open, 2025)
General Background: Character education has become a crucial agenda in Indonesian education policy, aiming to develop a generation embodying the noble values of Pancasila. Specific Background: Despite this emphasis, current classroom practices often prioritize cognitive knowledge over character development. Knowledge Gap: There is limited empirical evidence on the effectiveness of contextual learning models, particularly when mediated through concrete teaching tools, in shaping student character at the elementary level. Aims: This study investigates the implementation of the Contextual Teaching and Learning (CTL) approach using media to foster character development among 5th-grade students at SD Muhammadiyah 18 Plus Surabaya. Results: Findings demonstrate that media-based CTL effectively cultivates critical thinking, independence, cooperation, and creativity. Data revealed that over 50% of students reached the “Very Developed” level in character indicators aligned with the six dimensions of the Pancasila Student Profile. Novelty: This study introduces a contextual, media-supported character education model grounded in real-life student experiences, integrated with formative assessment and teacher facilitation strategies. Implications: The results suggest that sustained implementation of CTL can bridge academic learning and value transfer, supporting national character-building goals in primary education. Highlight : Integration with Real Life – CTL connects academic content to students' daily experiences, enhancing character development. Character Formation Focus – CTL strengthens traits like critical thinking, creativity, and cooperation through contextual strategies. Teacher as Facilitator – Teachers play a key role in designing meaningful, media-assisted, and character-oriented learning. Keywords : CTL, Media-Based Learning, Character Building, Elementary Education, Pancasila Profile